1H NMR Study of Mixed Micelles of Taurocholate and 1,2-Ethylene-di-N-n-propylcarbamate - WU, YI-HIAN; LIN, GIALIH (Asian Journal of Chemistry, 2010)
A combined model for the structures of the mixed micelles of taurocholate and 1,2-ethylene-di-N-n-propylcarbamate (1) has been proposed. Present model suggests that the structures of micelles of taurocholate are equally composed of these four dimeric fragments. Moreover, lipid molecules can only insert into back-to-back dimeric fragments but not into face-to-face dimeric fragments in the mixed micelles of taurocholate and lipid. To test this model, a short-chain analogue of glycerol lipid, 1,2-ethylene-di-N-n-propylcarbamate (1), was synthesized and was mixed with the micellar taurocholate to form the mixed micelle of taurocholate and compound 1. From the 1H NMR spectra, the a-methylene protons of compound 1 split after formation of the mixed micelle with taurocholate. Thus, half of compound 1 molecules insert into the antiparallel back-to-back dimers in the mixed micelle and the other half of compound 1 molecules insert into the parallel back-to-back dimers in the mixed micelle.